Historical and modern trends of spatial development of Russia: social and demographic aspects - Vadim A. Bezverbny; Nikolay Yu. Mikryukov; Timur R. Miryazov (Наука. Культура. Общество, 2020)
The article is devoted to the consideration of the spatial development of Russia in historical retrospective and at the present stage. The paper analyzes the definitions of the term “spatial development”, considers the trends in territorial and spatial development in the Russian Empire, the USSR and the Russian Federation, reflects current trends, and also shows the relevance of demographic processes in relation to ensuring sustainable development and preserving the country’s territories.